Socioeconomic differences in healthcare utilization, with and without adjustment for need: An example from Stockholm, Sweden. Issue 3 (May 2013) - Agerholm, Janne; Bruce, Daniel; Ponce de Leon, Antonio; Burström, Bo
Aim : Previous studies have shown varying degrees of inequity of utilization of healthcare in Sweden. Studies based solely on register data cannot take into account differences in health status while studies based solely on self-reported data from surveys may potentially have biased data on healthcare utilization. The aim of this study was to investigate socioeconomic differences in utilization of outpatient healthcare services in Stockholm County, comparing analysis based on only register data, with analysis based on health survey data linked to register data. Methods : We linked data from a public health survey in Stockholm County 2006 ( n = 34, 707) to register data on sociodemographic background characteristics and outpatient healthcare utilization in 2007. Negative binomial regression analysis was used to estimate income differentials in healthcare utilization adjusting for self-rated health and limiting longstanding illness. Results : Income differentials in the number of visits to doctors were found in favour of lower-income groups among people aged 25–64 years when only controlling for age. When controlling for health status, income differentials in favour of higher-income groups were observed among men (all ages) and among women aged 65+ years, with higher-income groups having 11–49% more visits than the lowest income group. Conclusions : The findings suggest that health status should be taken into account when analysing socioeconomic differences in healthcare utilization. When using only register based data there is a risk of underestimating or disregarding differences.